The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5812/compreped.80853
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acupressure on Physiological Indicators of Pain in Children Undergoing Tonsillectomy: A Randomized, Single-Blind, Placebo-Controlled Trial Study

Abstract: Background: Tonsillectomy is regarded as one of the most commonly used pediatric surgical procedures whose anxiety-related consequences can bring about several changes in the physiological characteristics of children. Therefore, the use of low-cost anxietyrelieving techniques in this domain can be of utmost importance to stabilize vital signs in this age group. Objectives: Accordingly, the purpose of the present study was to investigate the effects of acupressure on physiological indicators of pain including r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…According to the World Health Organisation, acupuncture and acupuncture may be used to treat and relieve many symptoms and diseases in individuals. [7][8][9][10][11][12] Unfortunately, widespread use of acupressure is not common in Iran at the moment, and more research is needed on this discipline.…”
Section: Dietary Therapymentioning
confidence: 99%
“…According to the World Health Organisation, acupuncture and acupuncture may be used to treat and relieve many symptoms and diseases in individuals. [7][8][9][10][11][12] Unfortunately, widespread use of acupressure is not common in Iran at the moment, and more research is needed on this discipline.…”
Section: Dietary Therapymentioning
confidence: 99%
“…Adolescents and children play pivotal roles in a nation's advancement, their health being fundamental for a country's future [23][24][25][26][27]. Considering the Orem's self-care model's focus on individual abilities and needs, our study aims to evaluate the impact of Orem's self-care model on the quality of life among adolescents diagnosed with type 1 diabetes.…”
Section: │ Introductionmentioning
confidence: 99%
“…It has been proven to be effective in many medical and psychological disorders. In recent years, acupressure has been receiving more attention for anxiety management, and many randomized controlled trials [4][5][6][7][8][9][10][11][12][13] and reviews [14][15][16] have shown promising evidence for anxiety relief (Table 1). According to the Oxford grading of evidence, all reported studies strongly support the favorable effect.…”
mentioning
confidence: 99%